Nature positive solutions for shifting agrifood systems to more resilient and sustainable pathways (Work Package 3: Restore) - Chavan, Sangram B.; Rajagopal, V.; Halli, H.M.; Viswadev, V.S.; Rajashri, Joshi (2024)
The project “Nature Positive Solutions for Shifting Agrifood Systems to More Resilient and Sustainable Pathways (Work Package 3: Restore)” focuses on the development of agroforestry models designed to restore degraded lands in the Akole cluster of Maharashtra, with an emphasis on enhancing both nutritional and environmental security. The project addresses several challenges, including soil erosion, fodder scarcity, and reduced tree cover. Agroforestry systems such as block plantations, silvipasture, and integrated farming were implemented to restore these degraded lands. The collaboration with BAIF, Pune along with CGIAR partners The Alliance Bioversity International-CIAT and International Water Management Institute, carried out this study with focus on the impact of restoration interventions on biodiversity, soil health, and carbon sequestration. A micro-watershed of about 63 hectare was identified in Chicondi village to implement technological interventions. The activities carried out under this project include the successful establishment of three agroforestry models—Fodder, Wadi, and Bamboo—on farmers' fields in Chichondi Village. Species like Mango and Bamboo were identified as priority species for plantation, with fodder scarcity being the most critical issue, as indicated by the constraints ranking. The Wadi system, dominated by Mango and Teak, played a key role in addressing both nutritional needs and environmental security. These systems also contributed significantly to biomass, carbon sequestration, and oxygen production. A comprehensive biodiversity assessment revealed significant variation in species richness and diversity across different land-use systems. The Bamboo system (New) exhibited the highest biodiversity, with a Shannon-Wiener Index of 3.7225 and species richness of 77, while the Agriculture Fallow system had the lowest biodiversity (Shannon-Wiener Index = 2.6469, Species Richness = 19). These findings underscore the importance of habitat-specific conservation strategies to maintain ecosystem health and support biodiversity. Soil properties showed variations in soil parameters, including pH, electrical conductivity, organic carbon content, nitrogen, phosphorus, and potassium levels across the systems. Soil pH ranged from 5.09 in the Wadi Control system to 6.51 in the Forest system, while organic carbon content varied from 0.55% in the Wadi Control system to 1.90% in the Forest system. These variations highlight the significant role of different agroforestry systems in improving soil health. Carbon sequestration studies showed that forest systems had the highest carbon stock at 112.9 Mg/ha, followed by agricultural fallow systems at 94.61 Mg/ha and Wadi systems at 75.34 Mg/ha. The Wadi control system, lacking tree cover, had the lowest carbon stock at 46.01 Mg/ha. Wadi agroforestry systems, dominated by Mango and Teak, significantly contributed to carbon sequestration, with 16.60 Mg/ha of carbon stock and 4.32 Mg/ha of CO₂ sequestration. These systems also produced 20.91 Mg/ha of oxygen, with Mango contributing 9.01 Mg/ha and Teak 8.06 Mg/ha. These findings highlight the key role of Wadi (Old) systems in restoring degraded lands, increasing tree cover, and improving carbon sequestration. Therefore, development of Agroforestry systems is vital in restoring ecosystems, boosting biodiversity, and mitigating climate change, while also providing sustainable income opportunities for local communities, ensuring long-term environmental sustainability and resilience.